2005
DOI: 10.1051/0004-6361:20052969
|View full text |Cite
|
Sign up to set email alerts
|

W Hya through the eye of Odin

Abstract: Abstract. We present Odin observations of the AGB star W Hya in the ground-state transition of ortho-H 2 O, 1 10 − 1 01 , at 557 GHz. The line is clearly of circumstellar origin. Radiative transfer modelling of the water lines observed by Odin and ISO results in a mass-loss rate of (2.5 ± 0.5) × 10 −7 M yr −1 , and a circumstellar H 2 O abundance of (2.0 ± 1.0) × 10 −3 . The inferred mass-loss rate is consistent with that obtained from modelling the circumstellar CO radio line emission, and also with that obta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(78 citation statements)
references
References 37 publications
(48 reference statements)
8
69
1
Order By: Relevance
“…The upper limit implied by the cosmic abundances of carbon and oxygen is no more than 1 × 10 −3 , assuming that all carbon is locked in CO and the remaining oxygen goes into H 2 O (Anders & Grevesse 1989). Vaporization of icy bodies (Justtanont et al 2005) or grain surface reactions via Fischer-Tropsch catalysis (Willacy 2004) will also result in a higher water abundance. Considering the agreement between the derived and the TE abundance, the effects of the other processes seem negligible for IK Tau.…”
Section: Resultsmentioning
confidence: 99%
“…The upper limit implied by the cosmic abundances of carbon and oxygen is no more than 1 × 10 −3 , assuming that all carbon is locked in CO and the remaining oxygen goes into H 2 O (Anders & Grevesse 1989). Vaporization of icy bodies (Justtanont et al 2005) or grain surface reactions via Fischer-Tropsch catalysis (Willacy 2004) will also result in a higher water abundance. Considering the agreement between the derived and the TE abundance, the effects of the other processes seem negligible for IK Tau.…”
Section: Resultsmentioning
confidence: 99%
“…For the molecular line excitation analysis well-tested, non-LTE and non-local, spectral line radiative transfer codes (based on the Monte Carlo and ALI methods), as presented in Schöier & Olofsson (2001), Justtanont et al (2005) and Maercker et al (2008Maercker et al ( , 2009) are used. The codes have also been benchmarked to high accuracy against other non-LTE radiative line transfer codes (van Zadelhoff et al 2002;Maercker et al 2008).…”
Section: Radiative Transfer Analysismentioning
confidence: 99%
“…In the detailed modelling of circumstellar H 2 O line emission for a number of M-type AGB stars, observed using the ISO and Odin satellites, the derived ortho-H 2 O abundances are ∼10 −4 (Justtanont et al 2005;Maercker et al 2008Maercker et al , 2009). The recent analysis of Herschel data of the M-type AGB star IK Tau confirms this (Decin et al 2010c).…”
Section: Introductionmentioning
confidence: 99%
“…We include these non-LTE effects by using an accelerated lambda iteration scheme (ALI, Rybicki & Hummer 1991) to solve the radiative transfer in a spherically symmetric model cloud. The ALI code we employed is the same as that used and tested by Justtanont et al (2005) and Maercker et al (2008). For the Sgr B2 cloud, we adopt the size, as well as gas and dust physical parameters for the envelope, provided by Zmuidzinas et al (1995), since those reproduce the observed continuum level around 557 GHz.…”
Section: Watermentioning
confidence: 99%